Understanding the impacts of post-wildfire process-based restoration on sediment accumulation and transient groundwater storage in a Colorado headwater stream - Jones, Brady, author; Morrison, Ryan, advisor; Bailey, Ryan, committee member; Rathburn, Sara, committee member (Colorado State University. Libraries, 2025)
Low-tech, process-based restoration (LTPBR) techniques are increasingly being implemented in headwater streams, especially in catchments affected or threatened by wildfire. Although many benefits of LTPBR have been thoroughly demonstrated, the influence of these restoration approaches on transient groundwater response and sediment size and storage following a wildfire are not well understood. This study focused on Elkhorn Creek, a small headwater stream (~4.5 km2), consisting of a low-gradient beaver meadow in the Cache la Poudre River watershed that burned during the 2020 Cameron Peak Fire. The efficacy of LTPBR techniques was assessed, including Post-Assisted Log Structures (PALS), which were implemented at the study site. Groundwater monitoring wells were installed throughout the study reach and in a reference reach located downstream. Sediment surveys including pebble counts and sediment probing were also conducted. Groundwater monitoring wells showed an average increase in groundwater elevation of 0.21 m in the study reach during baseflow one-year post-restoration when compared to limited data pre-restoration. Pebble counts showed a decrease in D50 of 11.7 mm one-year post-restoration. Sediment probing surveys showed approximately 63 m3 of sediment retention within the channel one-year post-restoration. Field data were then used to develop a linked hydrodynamic (SRH-2D) – groundwater (MODFLOW-NWT) model to observe the impacts of varying restoration scenarios involving location and number of PALS at varying flowrates on surface water volume and groundwater volume. Surface water volume results from the hydrodynamic model showed an increase of up to 37.4% when compared to no restoration implemented. Groundwater volume differences showed up to an 8% increase during low flows when comparing the groundwater volume difference to the least intensive restoration scenario to the most intensive restoration scenario. The linked hydrodynamic-groundwater model indicates that the greatest increase in both the surface water stage and inundation extent as well as the groundwater table elevations occurs at low and intermediate flows.
Keywords: numerical modeling; river; wildfire; restoration; groundwater; sediment